Challenges and strategies in developing human resources for the halal industry: Evidence from Indonesia - Sri Budi Cantika Yuli; Edyta Wojtyla (Journal of Innovation in Business and Economics, 2020)
The government has prioritized the development of the halal industry sector in Indonesia through the launch of the Indonesian Sharia Economics Master Plan (MEKSI) in 2019. Currently, Indonesia is in the 5th position in the world halal industry ecosystem. This is the main focus to strengthen Indonesia as a world halal producer in 2024. This study aims to examine the challenges of developing halal industry in Indonesia and try to provide a strategy for developing human resources (HR). This study applies a qualitative research approach using three stages of data analysis, namely data reduction, data presentation, and data verification. Data analysis techniques are supported by the NVivo 12 plus program. Based on the results of the literature study, several challenges were found related to the halal industry in Indonesia, i.e. Regulation, Human Resources (HR), Government, Infrastructure and Organization. This study compiles a human resource development strategy to face HR challenges, as follows 1) Human Resource Transformation through people transformation, cultural transformation, organizational transformation and 2) Human Resource Digitalization.